Trust the plan : the rise of QAnon and the conspiracy that unhinged America - Sommer, Will, 1988- (Harper, an imprint of HarperCollinsPublishers, 2023)
A journalist who has followed the rise of QAnon explains what it is, how it has gained a mainstream following among Republican lawmakers and ordinary citizens, the threat it poses to democracy, and how we can reach those who have embraced the conspiracy and are disseminating its lies.